Effect of Reduction Treatment on CO Oxidation with CeO2 Nanorod‐Supported CuOx Catalysts. Issue 1 (9th November 2017) - Mock, Samantha A.; Zell, Elizabeth T.; Hossain, Shaikh T.; Wang, Ruigang
Abstract: Understanding the correlation of thermal treatment with catalyst activity provides mechanistic information about how the catalysts can be activated or deactivated. In this paper, we report that a comparative study was conducted on CeO2 nanorod‐supported CuO x catalysts before and after reduction treatment to gain insight on the effects of the copper oxidation state and catalyst–support interfacial interactions on CO oxidation. X‐ray diffraction, Raman spectroscopy, hydrogen temperature‐programmed reduction (H2 ‐TPR), and transmission electron microscopy (TEM) were used in a comprehensive way to study the effects of CuO x (0≤ x ≤1) composition as well as their spatial distribution on CeO2 nanorods on the H2 consumption and CO oxidation of the catalysts. These techniques were then used to gain a better understanding of the correlation between the different copper species (α, β, and γ‐type CuO x ) and the multiple reduction (H2 consumption) peaks, found in the H2 ‐TPR data during the first run and during in situ reduction and redox cycling experiments. Also concluded from this study is that an abundance of surface defects are found on CeO2 nanorods from high‐resolution TEM, which consequently may be critical to strong CuO x (0≤ x ≤1)–CeO2− x (0≤ x ≤0.5) interactions, therefore resulting in the improved low‐temperature catalytic activity. Abstract : Effect of reduction treatment : A comparative study was conducted on CeO2 nanorod‐supported CuO x catalysts before and after reduction treatment to gain insight on the effects of the copper oxidation state and catalyst–support interfacial interactions on CO oxidation. An abundance of surface defects are found on CeO2 nanorods from high‐resolution TEM, which consequently may be critical to strong CuO x (0≤ x ≤1)–CeO2− x (0≤ x ≤0.5) interactions, therefore resulting in the improved low‐temperature catalytic activity.